How effective is cross-sector cooperation and community empowerment during the Covid-19 pandemic? Efforts to handle stunting in Karangsari Village of Kulon Progo - Nur Intan Kartika Sari (Berita Kedokteran Masyarakat, 2021)
Objective: This paper reviewed the effectiveness of cross-sectoral cooperation and community empowerment to handle stunting during the COVID-19 Pandemic in Karangsari Village, Pengasih District, Kulon Progo Regency. Content: Kulon Progo has been appointed by the central government as one of the stunting locus regency since 2017. The criterias that make Kulon Progo as a stunting locus regency is not only by the high prevalence of stunting (16.38% in 2017). But Kulon Progo is an area that has the best practices and high commitment from the local government. The prevalence of stunting in Kulon Progo continues to decline from 14.31% (2018) to 12.57% (2019). However, Kulon Progo Regency Government targets Kulon Progo becomes Zero Stunting at 2030. Among 10 villages in Kulon Progo that were chosen as stunting locus, one of them is Karangsari Village. Karangsari is a village that has high prevalence of stunting by 24.13% (2017) then decreased to 21.07% (2018). COVID-19 pandemic becomes a challenge to run the policy to handle stunting effort. Various efforts such as cross-sector cooperation and community empowerment continue to be carried out. Community empowerment includes Community Cadre Health Training, Non-Smoking Areas, Tari Gemayur and Community-Based Total Sanitation (CBTS). Those stunting handling efforts proved effective. Karangsari Village was crowned as the best CBTS village in Kulon Progo and the prevalence of stunting decreased from 13.72% (2019) to 9.88% (2020). Conclusion: The key of handling stunting efforts is the involvement of the government and cross-sectoral cooperation as well as the capacity of the community to carry it out.